The role of levonorgestrel intrauterine systems in the treatment of symptomatic fibroids - Wrona, Wojciech; Stępniak, Anna; Czuczwar, Piotr (Menopause Review/Przegląd Menopauzalny, 2017)
Uterine fibroids are considered to be the most frequently occurring tumours in females. The majority of fibroids do not require any treatment. When symptomatic, the major ailments include abnormal uterine bleeding, painful menstruation, pelvic pressure or pain, urinary problems, constipation, infertility, and recurrent pregnancy loss. Surgery remains a mainstay of symptomatic uterine fibroids therapy; however, minimally-invasive techniques and pharmacological management have become more available. The levonorgestrel intrauterine system (LNG-IUS) is a T-shaped device with a vertical stem containing a reservoir of levonorgestrel and is widely known for its contraception effect. Moreover, the non-contraceptive benefits of the LNG-IUS have been previously confirmed by numerous studies. LNG-IUS causes reduction of the duration and the amount of menstrual bleeding, with minimal side effects due to release of hormones at the targeted organ. Currently, results from systematic reviews show that LNG-IUS may be an effective and safe treatment for symptomatic uterine fibroids in premenopausal women. However, further studies are required to consolidate the usage of LNG-IUS in the treatment of symptomatic uterine fibroids.